Perbandingan Visualisasi Motif Kalpataru pada Berbagai Candi Peninggalan Mataram Kuno Abad 8-10 Masehi - Rosalinda, Herliyana; Amzy, Nurulfatmi; Limbong, Edo Galasro (Department of History, Faculty of Humanities, Diponegoro University, 2024)
This study examines the diverse visualizations of the Kalpataru motif in ancient Mataram temples. As significant religious symbols, these temples embodied societal values and were constructed with meticulous attention to materials, architecture, and aesthetics. By chronologically comparing the Kalpataru motif in Hindu and Buddhist temples, this research explores its evolving meaning and form. The Kalpataru, representing purity and sacredness in Hindu-Buddhist thought, appears prominently in temples such as Borobudur, Mendut, Pawon, Prambanan, and Sojiwan. While its origins lie in Buddhist symbolism, associated with Siddhartha Gautama's enlightenment, the motif underwent significant transformation in Hindu temples, particularly Prambanan, where it became more decorative and incorporated animal figures. This study employs a historical methodology, encompassing heuristic, critical, interpretive, and historiographical stages, to analyze these changes and their implications for understanding ancient Mataram culture.